On Fixed Point Findings for Diverse Contractions in b Dislocated-Multiplicative Metric Spaces - A. Kamal; Asmaa M. Abd-Elal (Journal of Mathematics)
In our present research study, we present the idea of b dislocated-multiplicative metric space (abbrev. bd-multiplicative metric space) that is generalization of b-multiplicative metric space and dislocated-multiplicative metric space. Furthermore, we prove some of the fixed point theorems in bd-multiplicative metric spaces. Also, we get common fixed point findings for fuzzy mappings in these spaces. Our findings are improved and more generalized form of several findings (see, e.g., [5, 6]).